G61 A five-year retrospective review of the management of childhood encephalitis. (27th April 2015) - Iro, MA; Hulbert-Powell, E; Ling, S
Abstract : Background: Early diagnosis and institution of appropriate treatment are key to improving outcomes from encephalitis. This study aimed to review the management of children with encephalitis in South East England. Methods: A retrospective review of clinical notes and electronic patient records (EPR) was conducted in between April 2013 and January 2014 across four hospitals (3 district general and 1 tertiary). Children aged 0–17 years who were admitted between 2008 and 2012 and had a discharge diagnosis of encephalitis were identified through the clinical coding department. Data on clinical features, investigation and treatment were collected. Findings: Medical records of thirty-four children were reviewed. A lumbar puncture was performed in 31 (91%) cases. A complete CSF order set (defined as CSF: white cell count, red blood cell count, gram stain, paired CSF and serum glucose and protein level) was requested in 21/30 (70%) cases. A complete PCR panel (CSF sent for the 3 main viral causes of encephalitis: enterovirus, herpes simplex and varicella zoster virus) was performed in 20/30 (67%) cases. The median time to performing a brain CT scan was 24 h (range 23–168) and 48 h (range 24–240) for brain MRI scan. The first dose of intravenous aciclovir was administered within 48 h for thirty-three (97%) cases. The prescribed aciclovir dose was incorrect in fifteen (44%) cases. The median duration of aciclovir treatment for children with enteroviral (EV) encephalitis was 5 days (IQR 2.5–5). The median length of hospital stay for the EV encephalitis group was 6 days (IQR 5.8–7.3). Six children with EV encephalitis received aciclovir treatment beyond 48 h due to non-availability of PCR test result. Children with EV encephalitis had a further median stay of 1.5 days (IQR 1.0–3.8) after availability of PCR result. Conclusion: The management of childhood encephalitis is heterogeneous. The recently published UK guidelines may help standardise practice. Widespread availability of PCR testing across hospitals and improved turnaround time could lead to early diagnosis and substantial cost saving from reduced hospital stay for infants with enteroviral encephalitis. Urgent steps are needed to reduce intravenous aciclovir prescribing errors.